Genetic structure of Carcinus maenas within its native range: larval dispersal and oceanographic variability - Domingues, Carla P. (2020)
Unravelling the interactions between life-history strategies and oceanography is central to our understanding of gene flow and connectivity in the marine environment. In the present study, we investigated the population genetic structure of the shore crab in its native range in relation to oceanographic characteristics and dispersal potential. Using 10 microsatellite markers over 2 yr, we surveyed 18 locations distributed along ~4200 km within the species native range, from Sweden to Morocco, assessed the population structure by means of FST and Bayesian clustering analysis and tested the hypothesis of isolation-by-distance (IBD) with a Mantel test. We focused particular attention along a 1200 km stretch of the Iberian Peninsula. We found no evidence of genetic structure (FST = 0.0001, p > 0.05) along the Iberian coast, and patterns were temporally stable over 2 yr. Across the more extensive geographic spatial scale, overall genetic differentiation was low (FST = 0.001) but statistically significant (p < 0.001). Furthermore, clustering analysis grouped the samples into 3 genetic units from (1) Sweden, (2) Wales and the Iberian Peninsula and (3) Morocco. While the correlation between genetic and geographic distances was significant, the pattern was not consistent with an IBD pattern. Results suggests that, in the absence of barriers to gene flow, shore crab populations are genetically similar across thousands of kilometres, but isolated populations still may occur within the species native range. Local oceanography and larval behaviour may have a significant influence on the structuring of the populations under study.